Corporate Social Responsibility and Financial Performance in Nepalese Commercial Banks - Panthi, Top Lal (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2023)
In this study, the effect of corporate social responsibility on total assets, proxy of financial performance with a mediating variable number of employees in Nepalese commercial banks, has been examined to fulfill the objective of identifying the size, trend and status of corporate social responsibility and analyzing the effect of CSR with a mediating variable number of employees on total assets. An aggregate level of CSR with a mediating variable number of employees have been applied as the independent variable and total assets have undertaken as the dependent variable in the research framework. Panel data sets from seventeen Nepalese commercial banks for ten years have been observed and tested using correlation coefficients and regression models under the approach of descriptive and analytical research design, to determine the effect of CSR with a mediating variable number of employees of the organization on the total assets. The findings postulate that the increasing trend of CSR expenditure made by the banks and total assets have a significant positive relationship. From the analysis, it has concluded that there is a positive relationship between the variables and the impact of CSR on total assets, symbolizes increasing in CSR leads to an increase in the financial performance of the organization. Furthermore, it raises the public image of the firm and attracts more investors which creates sustainable growth over the competition. This study demands the implication of CSR practices for all the business organization even if not mandatory from the concerned department.